The Effect Of Special Exercises On Learning Hurdle Clearing And The Rhythmic Triple Step Of 100m Hurdles Aged 14 – 15 Years Old - Hassan, Mohammed; Haitham, Ahmed (Journal of Physical Education, 2018)
The Effect Of Special Exercises On Learning Hurdle Clearing And The Rhythmic Triple Step Of 100m Hurdles Aged 14 – 15 Years OldThe importance of the research lies in identifying the effect of special exercises using teaching aids for learning the basic phases of hurdles; clearance and rhythmic triple steps. The problem of the research lies in the lack of interest in training these two phases. The researchers came up with some conclusions and recommendations.Keywords: special exercises, hurdles, clearing.